STUDY OF MECHANISMS OF FUNCTIONING AND DEVELOPMENT OF THE ANTI-TERRORISM SECUR - Biela, S.; Matsiuk, V.; Yevtushenko, I. (Honor and Law, 2020)
The article examines the theoretical and methodological foundations of the functioning of the anti-terrorist security system in Ukraine. It is established that the latest strategic and conceptual legal acts of Ukraine define terrorism as one of the main threats to national security of Ukraine. Before, the threat of terrorism in Ukraine was expected from outside activities of international terrorist organizations. However, the peculiarities of the hybrid confrontation in the South-East of Ukraine since the spring of 2014 have shown terrorist threats of a new form. The aim of the article is to study the theoretical and methodological foundations of the functioning of the anti-terrorist security system in Ukraine and substantiate the relevant development mechanisms. In order to determine the real situation in the field of terrorist threats, the article pays attention to the accounting of criminal offenses in recent years. Statistics show that the largest number of terrorist threats in Ukraine arose in the period from the beginning of the anti-terrorist operation to the beginning of the joint force operation. In order to study the best practices of Ukraine in the functioning of the anti-terrorist security system of Ukraine during the anti-terrorist operation in some districts of Donetsk and Luhansk regions, a survey of experts in the field of anti-terrorist security of Ukraine was conducted. The results of the survey provided an opportunity to identify the main issues of the anti-terrorist security system and provide proposals for improving the regulatory framework for the organization of combat missions of the security and defense sector, improving the organization of management, interdepartmental cooperation, improving the level of early training of the staff, clear definition of tasks for units of the security and defense sector and improvement of comprehensive support for the activities of the components of the security and defense sector during the implementation of anti-terrorist operations. Areas of further research will be aimed at developing mechanisms for the development of anti-terrorist security system of Ukraine.